Interaction and Subcellular Association of PRRT1/SynDIG4 With AMPA Receptors - Martin, Emily Eischen; Wleklinski, Erica; Hoang, Hanh T. M.; Ahmad, Mohiuddin (Frontiers in Synaptic Neuroscience, 2021)
AMPA receptors (AMPAR) are organized into supramolecular complexes in association with other membrane proteins that provide exquisite regulation of their biophysical properties and subcellular trafficking. Proline-rich transmembrane protein 1 (PRRT1), also named as SynDIG4, is a component of native AMPAR complexes in multiple brain regions. Deletion of PRRT1 leads to altered surface levels and phosphorylation status of AMPARs, as well as impaired forms of synaptic plasticity. Here, we have investigated the mechanisms underlying the observed regulation of AMPARs by investigating the interaction properties and subcellular localization of PRRT1. Our results show that PRRT1 can interact physically with all AMPAR subunits GluA1-GluA4. We decipher the membrane topology of PRRT1 to find that contrary to the predicted dual membrane pass, only the second hydrophobic segment spans the membrane completely, and is involved in mediating the interaction with AMPARs. We also report a physical interaction of PRRT1 with phosphatase PP2B that dephosphorylates AMPARs during synaptic plasticity. Our co-localization analysis in primary neuronal cultures identifies that PRRT1 associates with AMPARs extrasynaptically where it localizes to early and recycling endosomes as well as to the plasma membrane. These findings advance the understanding of the mechanisms by which PRRT1 regulates AMPARs under basal conditions and during synaptic plasticity.